Acoustic guided wave techniques for detecting corrosion damage of electrical grounding rods. (December 2019) - Zhao, Junhui; Durham, Nicholas; Abdel-Hadi, Karim; McKenzie, Colin Aird; Thomson, Douglas J.
Graphical abstract: Highlights: Acoustic guided waves are effective for corrosion detection in buried rods. Detection is effective even with high acoustic losses due to surrounding soil. Frequencies between 20 and 100 kHz have proven to be the most useful. Separate transducers for launch and receive are more effective. Abstract: Determining the integrity of grounding electrodes is challenging and there is need to augment expensive and time consuming excavation based methods. In this work pulse-echo methods based on acoustic guided waves were tested on model ground rods with machined model corrosion pits. The generation and propagation of the guided acoustic waves in the model grounding rods using different types of acoustic wave emitters and sensors was studied. The existence of three principle wave modes, longitudinal, flexural and torsional modes, was experimentally observed. The experimentally obtained group velocities versus frequency are consistent with numerical simulations. The principal longitudinal mode at low frequencies has been identified as the best candidate for damage detection on the grounding rods. The pulse-echo signals from the simulated corrosion pits are well correlated with the positions and cross-sectional areas of the pits. Wet-clay wrapping of the rods was used to simulate the influence of soil on the wave propagation. In the wet clay wrapped rods pulse-echo signals from the simulated corrosion pits are well correlated with the positions and cross-sectional areas of the pits, despite the significant attenuation of the echo signals. Acoustic pulse-echo methods based on acoustic guided waves have potential practical application for detecting corrosion-damage of the grounding rods.